Phytochemical studies and bioactivities of xylopia ferruginea hook. (annonaceae) and shorea maxwelliana king (dipterocarpaceae) / Nik Khairunissa' Nik Abdullah Zawawi - Nik Abdullah Zawawi, Nik Khairunissa (2012)
In the present work, phytochemical studies were conducted on two species from different family. The studied plant samples were the stem bark and leaves of Xylopia ferruginea; and the stem bark of Shorea maxwelliana. Phytochemical investigation on the crude alkaloidal extracts of the stem bark and leaves of this plant yielded five oxoaporphinoid alkaloids and three flavonols, characterised as O-methylmoschatoline, lysicamine, liriodenine, atherospermidine, oxostephanine, quercetin, kaempferol and afzelin. Phytochemical investigation carried out on the stem bark of Shorea maxwelliana King has yielded five oligostilbenoids identified as a-viniferin, maximol A, vaticanol A, suffruticosol A and vaticanol G. Structure elucidation and characterization of isolated compounds were done based on ID, 2D NMR, IR, UV, MS, optical rotation, melting point and in good agreement with those previously reported for these compounds. In addition, the antibacterial activity of major isolated compounds was tested against seven bacteria. Our findings showed that (9-methylmoschatoline is the most active compound as it inhibited the growth of all tested bacteria and the highestinhibition were shown in S. aureus (20 mm) and S. epidermis (23 mm). Vaticanol G showed moderate and slight activity against S. aureus and E. coli, while maximol A exhibited slight activity against E. coli and P. aeroginosa. Maximol A, suffruticosol A, vaticanol A and vaticanol G possessed active cyctotoxic activity against HL60 cell line with IC₅₀ values range of 10.1 - 220 μM.. Only maximol A was active against A549 and MCF-7 cell lines, with both IC₅₀ value of 220 and 99.2 μM.